Physico-chemical, sensory, and microbiological quality of raw chicken meat: an exploratory study in the Hisar city of Haryana, India - Bhawana, Indora; Malik, Ashok; Raposo, António; Singh, Shubha; Yadav, Sanjay; Zandonadi, Renata Puppin; Lho, Linda Heejung; Han, Heesup; Thakur, Neha (Frontiers in Nutrition, 2023)
A survey was conducted in Hisar city, which is located in Haryana, India, in order to assess the quality of raw chicken meat. Healthy broiler chickens were obtained from meat retail outlets from Hisar city in order to cover the entire city, which included most meat retail outlets. Also, a sample of control chicken was obtained from the Livestock Farm, College of Veterinary Sciences (LUVAS). The raw chicken meat was grouped into two categories, which included breast cut and thigh cut. The breast muscles, which include pectoralis major and pectoralis minor, and the thigh muscles, which include the abductor muscles, were chosen as the samples for proximate analysis, which included a physio-chemical, sensory, and microbiological analysis of raw chicken meat. The raw meat analysis in the laboratory revealed that parameters, such as proximate composition, pH, WHC, TBA, the instrumental color analysis, and the sensory evaluation presented inconsistent variations between the control and the retail samples. The moisture content of the control breast sample was significantly higher (p<0.05), which varied significantly with shops 2, 3, and 5, whereas it was statistically comparable to shops 1, 4, and 6. The control thigh sample had a significantly lower total plate and psychrotrophic count than shops 3, 4, 5, and 6 thigh samples. Shops 1, 2, 5, and 6 had significantly higher pH values than the control among the thigh pH values. The variations in the various parameters were multifactorial in origin and established a superiority of laboratory slaughtered birds grown on university farm in comparison to the raw chicken meat available at retail outlets in Hisar city.